XVIIth International Congress on Mathematical Physics 2013
DOI: 10.1142/9789814449243_0060
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic Derivation of the Ginzburg-Landau Model

Abstract: Abstract. We present a summary of our recent rigorous derivation of the celebrated Ginzburg-Landau (GL) theory, starting from the microscopic BardeenCooper-Schrieffer (BCS) model. Close to the critical temperature, GL arises as an effective theory on the macroscopic scale. The relevant scaling limit is semiclassical in nature, and semiclassical analysis, with minimal regularity assumptions, plays an important part in our proof.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…The validity of this approximation was discussed by Gor'kov [9] and, later, by de Gennes [7] and Eilenberger [2]. In our previous work [4] (see also [5,6]) we identified a precise parameter regime where this approximation is valid and we gave the first mathematical derivation of GL theory from BCS theory with quantitative error bounds. In this paper we continue our investigation and discuss the critical temperature in the BCS model.…”
Section: Introductionmentioning
confidence: 81%
See 3 more Smart Citations
“…The validity of this approximation was discussed by Gor'kov [9] and, later, by de Gennes [7] and Eilenberger [2]. In our previous work [4] (see also [5,6]) we identified a precise parameter regime where this approximation is valid and we gave the first mathematical derivation of GL theory from BCS theory with quantitative error bounds. In this paper we continue our investigation and discuss the critical temperature in the BCS model.…”
Section: Introductionmentioning
confidence: 81%
“…In [6] this was shown for D > 0, but in [8] it was remarked that the same proof works even for D ≤ 0, provided the normalization of α * is changed accordingly. …”
Section: Lemma 25 the Critical Value D C Is Uniquely Characterized mentioning
confidence: 89%
See 2 more Smart Citations
“…In a remarkable work, R. Frank, Ch. Hainzl, R. Seiringer, J.P. Solovej ( [132]) have shown that, for non-dynamical magnetic fields, the nanoscopic approximation of the BdG system is given by the Ginzburg-Landau one (see also [133,134,72]).…”
mentioning
confidence: 99%